2012
DOI: 10.1136/bjophthalmol-2011-301150
|View full text |Cite
|
Sign up to set email alerts
|

Can virtual reality simulation help to determine the importance of stereopsis in intraocular surgery?

Abstract: The importance of stereopsis for intraocular surgery is difficult to establish in a live theatre setting without compromising patient safety. Virtual reality simulators provide a safe alternative. This study demonstrates a statistically significant decrease in simulated intraocular surgical performance with acute loss of stereopsis in potential ophthalmic training applicants. Caution is recommend in using these results to advocate stereopsis testing as a screening tool in interviews because some participants p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…With the advent of virtual reality simulators it is now possible to study the effects of different conditions on surgical outcomes without compromising patient safety [7][8][9][10]. Simulators have been used to study how distractions can influence surgical outcomes [11], including during intraocular procedures involving the anterior segment by Park et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of virtual reality simulators it is now possible to study the effects of different conditions on surgical outcomes without compromising patient safety [7][8][9][10]. Simulators have been used to study how distractions can influence surgical outcomes [11], including during intraocular procedures involving the anterior segment by Park et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…2 Recent studies have demonstrated that a decreased stereoacuity results in a statistically significant decrease in simulated surgical performance for most participants. 3,4 We suggest that all ophthalmic simulatorbased studies should measure participant visual acuity and stereoacuity to ensure reliable results.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…It is, however, possible to do so with the use of an ophthalmic simulator, which we previously used to show other variables that cannot be observed on real patients, such as the effect of distraction, fatigue, and loss of stereopsis on surgical performance. [1][2][3] The aim of this study was to establish the safety of nondominant-hand simulated intraocular surgery.…”
mentioning
confidence: 99%